Lack of efficacy of mTOR inhibitors and ACE pathway inhibitors as antifibrotic agents in evolving and established fibrosis in Mdr2−/− mice. (10th March 2014) - Bridle, Kim R.; Sobbe, Amy L.; de Guzman, C. Erika; Santrampurwala, Nishreen; Jaskowski, Lesley A.; Clouston, Andrew D.; Campbell, Catherine M.; Nathan Subramaniam, V.; Crawford, Darrell HG
Abstract Background & Aims Mammalian target of rapamycin and angiotensin‐converting enzyme inhibition has been shown to have antifibrotic activity in models of liver fibrosis. The aim of our study was to determine the efficacy of rapamycin, everolimus, irbesartan and captopril, alone and in combination, as antifibrotic agents in the Mdr2−/− model of cholestasis both in early injury and established disease. Methods Mdr2 −/− mice were treated for 4 weeks with vehicle, rapamycin (1 mg/kg) or everolimus (5 mg/kg) every second day or with captopril (30 mg/kg/day), irbesartan (10 mg/kg/day) or vehicle. Further groups of 3‐week‐old Mdr2−/− mice were treated with rapamycin and irbesartan in combination (1 mg/kg/day and 10 mg/kg/day) or with rapamycin (2 mg/kg/day) for 4 weeks. Liver injury and fibrosis were compared between treated and untreated animals. Results There were no significant improvements in liver injury, histology, hepatic hydroxyproline or profibrogenic gene expression following treatment with rapamycin, everolimus, captopril or irbesartan at any time point studied. Likewise, there were no improvements in liver histology or profibrogenic gene expression following combination therapy or high‐dose rapamycin treatment. Conclusions The antifibrotic effects of rapamycin, everolimus, captopril and irbesartan seen in other models of fibrosis were not replicated in the Mdr2−/− model in this study. This highlights the clear need to test specific antifibrotic agents in a number of different animal models. We believe this animal model is ideal to study usefulness of antifibrotic agents in cholestatic liver disease because of the similarity in genetics and hepatic histopathology to human cholestatic liver disease.